Liquid compression mold material and electronic component using the same
The liquid compression mold material with epoxy resin, hardening agent, filler, and ion trap agents effectively reduces ionic impurities, addressing reliability issues in semiconductor packages by minimizing short-circuits and improving semiconductor element performance.
Patent Information
- Application Number
- JP2023114446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
AI Technical Summary
Conventional liquid compression mold materials for semiconductor packages contain high levels of impurities, particularly ionic impurities, which affect the reliability of semiconductor elements, especially as bump pitches narrow, leading to increased short-circuit risks and reliability issues.
A liquid compression mold material comprising epoxy resin, a hardening agent, filler, and an ion trap agent, specifically including bismuth-based or zirconium-based compounds, to capture and reduce chloride ions, with controlled viscosity and particle sizes, ensuring low impurity levels and improved reliability.
The material significantly reduces chloride ion concentration in the cured substance, enhancing the reliability of semiconductor elements by minimizing short-circuit occurrences and impurity effects, particularly in narrow pitch intervals.
Smart Images

Figure 2025011965000001 
Figure 2025011965000002 
Figure 2025011965000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid compression molding material that can be suitably used in the manufacture of electronic components, and to an electronic component, particularly a semiconductor package, that uses the liquid compression molding material. [Background technology]
[0002] Many semiconductor elements such as integrated circuits that constitute a semiconductor package are encapsulated with an encapsulant. Molding methods for encapsulating semiconductor elements can be roughly classified into (i) transfer molding, in which a molten curable resin composition is pressure-injected into a cavity through a flow path that supplies the resin composition such as a runner or gate into the cavity, and then cured, and (ii) compression molding, in which a granular or liquid curable resin composition is directly supplied onto a substrate or release film without passing through a flow path such as a runner or gate, and then cured. Among these molding methods, compression molding, which is more suitable for producing relatively large molded products, has been increasingly adopted for encapsulating semiconductor elements in recent years. This is due to the widespread use of wafer-level chip size packaging technology (which involves encapsulating a wafer that has not been cut into chips after circuit formation has been completed).
[0003] Conventional curable resin compositions used for sealing semiconductor elements by compression molding have mainly been solid resin compositions such as granular ones. However, recently, with the development of new compression molding techniques, liquid curable resin compositions are increasingly being used. Hereinafter, such liquid curable resin compositions used for sealing by compression molding are referred to as "liquid compression molding materials" (hereinafter, may be abbreviated as "LCM (Liquid Compression Molding) materials").
[0004] As a liquid compression molding (LCM) material, a liquid epoxy resin composition is often used from the viewpoint of a balance of various properties such as electrical properties, moisture resistance, heat resistance, mechanical properties, adhesiveness, etc. An example of an epoxy resin composition used as an LCM material is the liquid resin composition described in Patent Document 1.
[0005] As semiconductor elements become more compact and perform better, the bump pitch, which is the distance between wiring, tends to become narrower, even on the order of micrometers. If the pitch of wiring is narrow, short circuits and the like are more likely to occur, adversely affecting the reliability of the elements. The encapsulant for semiconductor elements is also filled between the pitch of the elements, and since the narrow pitch increases the possibility that impurities contained in the encapsulant will have an effect, encapsulants with low impurities are in demand. In particular, ionic impurities have a significant effect on electrical circuits, so methods such as using raw materials with reduced impurity ions (Patent Document 2) or adding materials that capture ions are used (Patent Documents 3 to 5). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2018 / 221681 [Patent Document 2] JP 2021-172793 A [Patent Document 3] JP 2001-279057 A [Patent Document 4] International Publication No. 2019 / 131669 [Patent Document 5] JP 2017-179185 A [Patent Document 6] JP 2015-105304 A Summary of the Invention [Problem to be solved by the invention]
[0007] As semiconductor devices become more sophisticated, electronic devices such as smartphones and personal computers are becoming lighter, thinner, shorter, and smaller. As a result, the bump pitch at the semiconductor junctions has become narrower, on the order of micrometers, and there is a need to provide LCM materials with higher reliability than ever before. Impurity ions contained in LCM materials can affect reliability, so LCM materials with low impurity ions are in demand.
[0008] In order to solve the above-mentioned problems of the conventional techniques, an object of the present invention is to provide an LCM material in which impurity ions in the cured product are suppressed. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention includes the following inventions, but is not limited to the following.
[0010] 1. (A) an epoxy resin; (B) a curing agent; (C) a filler; (D) an ion trapping agent, Liquid compression molding material.
[0011] 2. The liquid compression molding material according to item 1 above, wherein the (D) ion trapping agent includes at least one selected from the group consisting of bismuth-based compounds, zirconium-based compounds, and antimony-based compounds.
[0012] 3. The liquid compression molding material according to item 1 or 2 above, wherein the content of the ion trapping agent (D) is 0.2 to 7 parts by mass per 100 parts by mass of the epoxy resin.
[0013] 4. The liquid compression molding material according to any one of items 1 to 3 above, wherein the content of the (D) ion trapping agent is 1.2 to 2.4 parts by mass per 100 parts by mass of the epoxy resin.
[0014] 5. The liquid compression molding material according to any one of items 1 to 4 above, wherein the average particle size of the ion trapping agent (D) is 10 nm to 5 μm.
[0015] 6. The chloride ions (Cl) contained in the epoxy resin (A) - 6. The liquid compression molding material according to any one of items 1 to 5 above, wherein the amount of said component (I) is 2000 ppm or less.
[0016] 7. The liquid compression molding material according to any one of items 1 to 6 above, having a viscosity of 50 to 500 Pa·s when measured using a Brookfield HB-DV viscometer at a liquid temperature of 25°C and 20 rpm.
[0017] 8. The liquid compression molding material was crushed into 5 mm squares and hardened, and then compressed at 0.1 g / cm 3 8. The liquid compression molding material according to any one of items 1 to 7, wherein the chloride ion concentration in an extract obtained by immersing the liquid in water for 20 hours under an atmosphere of 121° C., 100% humidity and 2 atm is less than 2.5 ppm.
[0018] 9. A semiconductor package obtained by encapsulating a semiconductor element with the liquid compression molding material according to any one of items 1 to 8 above. Effect of the Invention
[0019] The liquid compression molding material of the present invention contains a reduced amount of impurity ions in the cured product, and can further improve the reliability of semiconductor elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail. The present invention relates to a composition comprising: (A) an epoxy resin; (B) a curing agent; (C) a filler; (D) an ion trapping agent, This invention relates to a liquid compression molding material. The above components (A) to (D) contained in the LCM material of the present invention will be described below. In this specification, a substance being "liquid" means that the substance is in a liquid state at 25°C. "Liquid" refers to a state of flowability, and preferably means a fluid having a viscosity of 0.001 to 1000 Pa·s measured at 25°C using an E-type viscometer. The above substance may be a pure substance or a mixture. This mixture may be in a homogeneous form such as a solution, or in a heterogeneous form such as an emulsion or suspension. In other words, unless otherwise specified, when a mixture is said to be liquid, it is sufficient that the mixture as a whole satisfies the above requirements, and it may contain a component that does not fall under the category of a liquid.
[0021] [Epoxy resin (component (A))] The LCM material of the present invention contains an epoxy resin, which may hereinafter be referred to as "component (A)." As component (A) in the LCM material of the present invention, an epoxy resin generally used as a semiconductor encapsulation material can be used, and the type is not particularly limited. The epoxy resin is preferably a multifunctional epoxy resin having two or more functionalities from the viewpoint of reliability against heat. Each epoxy group may be located at any position of the epoxy resin molecule. When the epoxy resin is a polymer, the epoxy group is preferably located at the end of the molecule, but may be located in other parts. For example, a monomer unit constituting the polymer may have an epoxy group, or a unit containing an epoxy group may be introduced into the polymer by graft modification to have an epoxy group in the side chain. Many are commercially available and are relatively easy to prepare, and from the viewpoint of curability, it is preferable that the molecule has at least two epoxy groups at both ends, and it is more preferable that the main skeleton of the molecule does not have a large branch and has epoxy groups at both ends.
[0022] The type of epoxy resin can be any of monocyclic aromatic epoxy resins, heterocyclic epoxy resins, alicyclic epoxy resins, resins in which a structure derived from a compound having a plurality of ring structures has been epoxidized, aliphatic epoxy resins, etc., without any limitations. That is, the portion that becomes the molecular skeleton of the epoxy resin is not particularly limited in structure, and can be linear, branched, cyclic including condensed rings, or a combination of these structures. The portion that becomes the molecular skeleton can have linear, branched, or cyclic aliphatic hydrocarbons, aromatic hydrocarbons, heterocyclic groups, or aromatic heterocyclic groups. Examples of structures constituting the molecules of epoxy resins include structures derived from monocyclic or polycyclic aromatic hydrocarbons such as benzene, naphthalene, phenanthrene, anthracene, indene, and fluorene, structures derived from aliphatic hydrocarbon rings such as cyclopentane, cyclohexane, cyclooctane, and norbornene, structures derived from heterocyclic structures such as pyridine, pyrazine, azepine, imidazole, oxazole, benzimidazole, quinoline, benzopyran, carbazole, xanthene, furan, tetrahydropyran, and thiophene, structures derived from linear or branched aliphatic hydrocarbons having 1 to 30 carbon atoms, preferably 1 to 20 carbon atoms, and more preferably 1 to 8 carbon atoms, as well as structures obtained by combining these structures, such as dimethylcyclohexane and 2,2-diphenylpropane. In addition, the molecular skeleton of an epoxy resin can be polymeric, such as the skeleton of polyethylene glycol (PEG), and may be interrupted at one or more points by heteroatoms such as oxygen, nitrogen, sulfur, and silicon. The position of the epoxy group in the molecular skeleton composed of these structures is not particularly limited, and at least a part of the hydrogen in the molecular skeleton may be substituted with a functional group such as a halogen, a carbonyl group, an amino group, a hydroxyl group, a silyl group, etc., as long as the curability as an epoxy resin is not hindered. The epoxy resin has an epoxy group at any position in the skeleton obtained by using the above elements alone or in combination, but it is preferable that the epoxy group is bonded to an aliphatic hydrocarbon group having one carbon atom, that is, that the epoxy resin has a glycidyl group (C2H4O-CH2-), originating from the step of introducing the epoxy group in the synthesis of the compound.In addition, the molecular skeleton of the epoxy resin, which is the methylene group of the glycidyl group, can be designed by chemical synthesis, but epoxy resins having skeletons derived from natural products may also be used, and these may be combined.
[0023] Examples of epoxy resins include monocyclic aromatic epoxy resins such as catechol diglycidyl ether, resorcinol diglycidyl ether, p-hydroxybenzoic acid diglycidyl ether ester, phthalic acid diglycidyl ester, terephthalic acid diglycidyl ester, 2,5-diisopropylhydroquinone diglycidyl ether, and hydroquinone diglycidyl ether, which have a cyclic structure; aminophenol-type epoxy resins such as triglycidyl-p-aminophenol; aniline-type epoxy resins such as diglycidylaniline; diglycidyl amine; Polyfunctional glycidylamine type epoxy resins such as toluidine type epoxy resins such as tetraglycidyldiaminodiphenylmethane type epoxy resins such as tetraglycidyldiaminodiphenylmethane type epoxy resins; heterocyclic epoxy resins such as triglycidyl isocyanurate and 1,3-diglycidyl-5-methyl-5-ethylhydantoin; 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexylcarboxylate, bis Alicyclic epoxy resins such as (3,4-epoxycyclohexyl) adipate, vinylcyclohexene monoepoxide, diepoxylimonene, vinyl(3,4-cyclohexene) dioxide, 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-m-dioxane, 1,4-cyclohexanedimethanol diglycidyl ether, tetraglycidyl bis(aminomethyl)cyclohexane, etc.; bisphenol A type, bisphenol F type, bisphenol AD type, bisphenol S type, diallyl bisphenol bisphenol type epoxy resins such as aryl A type and bisphenol type epoxy resins in which at least a portion of the rings of these epoxy resins have been hydrogenated; mixtures of oligomers obtained by partial polymerization of bisphenol type epoxy resins; tetramethylbis(4-hydroxyphenyl)methane diglycidyl ether, tetramethylbis(4-hydroxyphenyl)ether diglycidyl ether, polyarylene ether diglycidyl ether, and these biphenyl type or tetramethylbiphenyl type epoxy resins and resins in which at least a portion of the rings of these epoxy resins have been hydrogenated;Examples of the epoxy resin include fluorene-type epoxy resins such as bisphenolfluorene-type epoxy resins and biscresolfluorene-type epoxy resins; naphthalene-type epoxy resins such as 1,6-bis(glycidyloxy)naphthalene and β-hydroxynaphthoic acid diglycidyl ether ester; and dicyclopentadiene-type epoxy resins such as dicyclopentadiene dimethanol diglycidyl ether, which are obtained by epoxidizing a structure derived from a compound having a plurality of ring structures.
[0024] Examples of aliphatic epoxy resins include difunctional aliphatic epoxy resins having two epoxy groups in the molecule, such as alkylene glycol diglycidyl ether, poly(alkylene glycol) diglycidyl ether, and alkenylene glycol diglycidyl ether; polyfunctional aliphatic epoxy resins having three or more epoxy groups in the molecule, such as polyglycidyl ethers of trifunctional or higher alcohols (trimethylolpropane, pentaerythritol, dipentaerythritol, etc.) [trimethylolpropane triglycidyl ether, trimethylolmethane triglycidyl ether, trimethylolethane triglycidyl ether, pentaerythritol (tri- or tetra-)glycidyl ether, dipentaerythritol (tri-, tetra-, penta- or hexa-)glycidyl ether, etc.]; and glycidyl glycoluril compounds having two or more epoxy groups in the molecule, such as 1,3,4,6-tetraglycidyl glycoluril.
[0025] Of these aliphatic epoxy resins, difunctional aliphatic epoxy resins are preferred. Examples of difunctional aliphatic epoxy resins include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,3-propanediol diglycidyl ether, 2-methyl-1,3-propanediol diglycidyl ether, 2-butyl-2-ethyl-1,3-propanediol diglycidyl ether, 1,4-butanediol diglycidyl ether (tetramethylene glycol diglycidyl ether), neopentyl glycol diglycidyl ether, 3-methyl-2,4-pentanediol diglycidyl ether, 2,4-pentanediol diglycidyl ether, 1,5-pentanediol diglycidyl ether (pentamethylene glycol diglycidyl ether), diglycidyl ether), 3-methyl-1,5-pentanediol diglycidyl ether, 2-methyl-2,4-pentanediol diglycidyl ether, 2,4-diethyl-1,5-pentanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether (hexamethylene glycol diglycidyl ether), 1,7-heptanediol diglycidyl ether, 3,5-heptanediol diglycidyl ether, 1,8-octanediol diglycidyl ether, 2-methyl-1,8-octanediol diglycidyl ether, 1,9-nonanediol diglycidyl ether and other alkylene glycol diglycidyl ethers (alkanediol diglycidyl ethers);Examples of the polyalkylene glycol diglycidyl ethers (including oligoalkylene glycol diglycidyl ethers) include diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, tetraethylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, poly(ethylene glycol / propylene glycol) diglycidyl ether, ditetramethylene glycol diglycidyl ether, tritetramethylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, dipentamethylene glycol diglycidyl ether, tripentamethylene glycol diglycidyl ether, polypentamethylene glycol diglycidyl ether, dihexamethylene glycol diglycidyl ether, trihexamethylene glycol diglycidyl ether, and polyhexamethylene glycol diglycidyl ether.
[0026] In one embodiment, the difunctional aliphatic epoxy resin is a (poly)alkylene glycol diglycidyl ether, preferably a (poly)alkylene glycol diglycidyl ether having 1 to 20 alkylene glycol (alkyleneoxy) units, and more preferably a (poly)alkylene glycol diglycidyl ether having 1 to 20 alkylene glycol units and having 2 to 4 carbon atoms in the alkylene glycol units. In another embodiment, the difunctional aliphatic epoxy resin is a polyalkylene glycol diglycidyl ether having 2 to 20 alkylene glycol (alkyleneoxy) units, preferably a polyalkylene glycol diglycidyl ether having 2 to 20 alkylene glycol units and having 2 to 4 carbon atoms in the alkylene glycol units.
[0027] The molecular weight of the aliphatic epoxy resin (when the aliphatic epoxy resin is a polymer, the molecular weight is the number average molecular weight in terms of standard polystyrene measured by gel permeation chromatography (GPC) using tetrahydrofuran as an elution solvent) is not particularly limited, but is preferably 200 to 10,000, more preferably 200 to 1,200, further preferably 200 to 1,000, and particularly preferably 300 to 900.
[0028] In addition, other epoxy resins, for example, epoxidized polymers such as epoxidized polyolefins and urethane-modified epoxy resins, as well as epoxy resins having a silicone skeleton such as 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane and epoxy-modified organopolysiloxane compounds, can also be used.
[0029] The epoxy resin is preferably liquid and has a low viscosity. Specifically, the viscosity of the epoxy resin at 25°C is preferably 50,000 mPa·s or less, more preferably 40,000 mPa·s or less, even more preferably 30,000 mPa·s or less, and particularly preferably 20,000 mPa·s or less. It is not preferable to use biphenyl-type epoxy resins and novolac-type epoxy resins, which are solid at room temperature, alone, but they may be mixed with other liquid epoxy resins as long as the above viscosity conditions are satisfied.
[0030] Since the general manufacturing process of epoxy resin includes a step of introducing an epoxy group using epichlorohydrin as a raw material, chlorine may remain in the epoxy resin. The remaining chlorine may affect the semiconductor element as a chloride ion. In the present invention, the amount of chlorine is reduced by the ion trapping agent, but it is preferable to use an epoxy resin with a small amount of chlorine because the amount of chlorine in the entire LCM material is further reduced. For example, it is preferable to use an epoxy resin with a total chlorine amount of 4500 ppm or less, and it is more preferable to use an epoxy resin with a total chlorine amount of 2000 ppm or less. It is possible to mix and use an epoxy resin with a chlorine amount of more than 4500 ppm, but when the total mass of the (A) epoxy resin is 100 parts by mass, the content of the epoxy resin with a total chlorine amount of 4500 ppm or less is preferably 60 to 100 mass%, and it is more preferable that the total chlorine amount contained in the epoxy resin is 2000 ppm or less.
[0031] A more preferred specific example of the aliphatic epoxy resin is a compound represented by the following general formula (I), that is, a diglycidyl ether of (poly)tetramethylene glycol. [ka] (wherein n is an integer of 1 to 15).
[0032] As the compound represented by general formula (I), commercially available products such as "EPOGOSE PT (general grade)" (Yokkaichi Chemical Co., Ltd., diglycidyl ether of polytetramethylene glycol, number average molecular weight 700 to 800) and YX7400N (manufactured by Mitsubishi Chemical Corporation) may be used.
[0033] In the LCM material of the present invention, a single epoxy resin may be used as component (A), or two or more kinds of epoxy resins may be used in combination. In the present invention, it is particularly preferable that component (A) contains an aliphatic epoxy resin, and it is more preferable that the aliphatic epoxy resin contains a compound represented by the general formula (I). In addition, it is preferable that the number average molecular weight of the aliphatic epoxy resin is 200 to 1000.
[0034] The epoxy resin may be prepared by chemical synthesis, or a commercially available product that is marketed as an epoxy resin may be used. Examples of such epoxy resins include the exemplary compounds represented by the above general formula (I), as well as the jER (registered trademark) series (Mitsubishi Chemical Corporation), BPF type epoxy resin YDF series (Nippon Steel Chemical & Material Co., Ltd.), bisphenol A type liquid epoxy resin RE series (Nippon Kayaku Co., Ltd.), Denacol EX series (Nagase ChemteX Co., Ltd.), Epolite series (Kyoeisha Chemical Co., Ltd.), Adeka glycirol series (ADEKA), Adeka Resin EP series (ADEKA), fluorene-based epoxy resin OGSOL EG series (Osaka Gas Chemical Co., Ltd.), and Showfree (registered trademark) series (Resonac Co., Ltd.).
[0035] [Hardening agent (component (B))] The LCM material of the present invention contains a curing agent. This curing agent is not particularly limited as long as it can cure the above-mentioned epoxy resin (component (A)), except for phosphorus compounds that have the effect of opening the epoxy group ring. The curing process is also not limited, and curing agents that act catalytically, those that function as crosslinking agents, etc. can be used. Hereinafter, this curing agent may be referred to as "component (B)".
[0036] Examples of the component (B) used in the LCM material of the present invention include imidazole compounds, amine compounds, phenolic compounds, acid anhydrides, active ester resins, cyanate ester resins, etc. Among these, the imidazole compounds may be latent or in the form of a microencapsulated curing agent.
[0037] Examples of imidazole compounds include imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-methyl ... ,2-Dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole and other 2-substituted imidazole compounds; 2-phenyl-4,5-dihydroxymethylimidazole; 2-phenyl-4-methyl-5-hydroxymethylimidazole; 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole; 1-dodecyl- 2-Methyl-3-benzyl imidazolium chloride; 2-Methylimidazoline; Trimellitates such as 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate; 2,4-diamino-6-[(2-methyl-1-imidazolyl)ethyl]s-triazine, 2,4-diamino-6-[(2-undecyl-1-imidazolyl)ethyl]s-triazine, 2,4-diamino-6-[(2-ethyl-4-methyl-1- triazine ring-containing compounds such as 2,4-diamino-6-[(2-methyl-1-imidazolyl)ethyl]s-triazine; an isocyanuric acid adduct of 2-phenylimidazole, an isocyanuric acid adduct of 2-methylimidazole, an isocyanuric acid adduct of 2-phenyl-4,5-dihydroxymethylimidazole, and an isocyanuric acid adduct of 2-phenyl-4-methyl-5-hydroxymethylimidazole. Of these imidazole compounds, 2-phenyl-4-methylimidazole, 2,4-diamino-6-[(2-methyl-1-imidazolyl)ethyl]s-triazine, 2-phenyl-4-methyl-5-hydroxymethylimidazole (including its isocyanuric acid adduct), and the like are preferred.
[0038] As the microcapsule-type curing agent, for example, a dispersion in which an amine compound powder is dispersed in a liquid epoxy resin can be used. The amine compound may be selected from, for example, an aliphatic primary amine, an alicyclic primary amine, an aromatic primary amine, an aliphatic secondary amine, an alicyclic secondary amine, an aromatic secondary amine, an imidazole compound, and an imidazoline compound. The amine compound may be used in the form of a reaction product with a carboxylic acid, a sulfonic acid, an isocyanate, an epoxide, or the like. These compounds may be used alone or in combination of two or more. For example, the amine compound may be used in combination with its reaction product with a carboxylic acid, a sulfonic acid, an isocyanate, or an epoxide. The volume average particle size of the powder of the amine compound is preferably 30 μm or less, more preferably 5 μm or less. In addition, it is preferable that the powder of the amine compound has a melting point or softening point of 60° C. or more in order to suppress thickening at 25° C.
[0039] As the phenolic compound, a phenolic resin, particularly a novolac resin obtained by condensing a phenol or naphthol (e.g., phenol, cresol, naphthol, alkylphenol, bisphenol, terpene phenol, etc.) with formaldehyde, is preferably used. Examples of novolac resins include phenol novolac resin, o-cresol novolac resin, p-cresol novolac resin, α-naphthol novolac resin, β-naphthol novolac resin, t-butylphenol novolac resin, bisphenol A type novolac resin, xylylene modified novolac resin, decalin modified novolac resin, etc. Examples of other phenolic resins include dicyclopentadiene cresol resin, polyparavinylphenol, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, and poly(di-p-hydroxyphenyl)methane, etc.
[0040] Examples of the acid anhydride include phthalic anhydride, hexahydrophthalic anhydride, alkyl hexahydrophthalic anhydrides such as methyl hexahydrophthalic anhydride, tetrahydrophthalic anhydride, alkyl tetrahydrophthalic anhydrides such as trialkyl tetrahydrophthalic anhydride and 3-methyl tetrahydrophthalic anhydride, himic anhydride, succinic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. Among these, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride, etc. are preferred.
[0041] Examples of the amine compound include diaminodiphenylmethane, tetramethyldiaminodiphenylmethane, tetraethyldiaminodiphenylmethane, diethyldimethyldiaminodiphenylmethane, dimethyldiaminotoluene, benzylmethylamine, m-xylylenediamine, methanephenylenediamine, diaminodibutyltoluene, diaminodipropyltoluene, diaminodiphenylsulfone, diaminoditolylsulfone, diethyldiaminotoluene, bis(4-amino-3-ethylphenyl)methane, polytetramethylene oxide-di-p-aminobenzoate, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, 4,4-dimethylaminopyridine, 2,4-diamino-6-(2'-methylimidazolyl)ethyl-1,3,5-triazine, etc. Among these, bis(4-amino-3-ethylphenyl)methane, 2,4-diamino-6-(2'-methylimidazolyl)ethyl-1,3,5-triazine, etc. are preferred. Further examples of the amine compound include triethylenediamine, diethylamine, triethylamine, diethylenetriamine, diethylenetetramine, dipropylenediamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, menthenediamine, isophoronediamine, 1,3-bisaminomethylcyclohexane (1,3-BAC), piperidine, N'N'-dimethylpiperazine, etc. The nitrogen-containing compound such as the imidazole compound or amine compound may be an amine adduct. As the adduct, an epoxy adduct type compound in which an epoxy group is partially added to an amino group can be used.
[0042] Preferred examples of the active ester resin include a resin containing a dicyclopentadiene-phenol addition structure, a resin containing a naphthalene structure, an acetylated product of phenol novolac, and a benzoylated product of phenol novolac.
[0043] Preferred examples of cyanate ester resins include bisphenol-type cyanate ester resins; cyanate ester resins of phenylene ether, naphthylene ether, biphenyl, anthracene, tetramethylbiphenyl, triphenylmethane, tetraphenylethane or polyhydroxynaphthalene; cyanate ester resins such as phenol novolac, cresol novolac and naphthol novolac; dicyclopentadiene-phenol addition reaction type cyanate ester resins; phenol or naphthol aralkyl type cyanate ester resins; and aromatic hydrocarbon formaldehyde resin modified phenol resins.
[0044] In the LCM material of the present invention, a single curing agent may be used as component (B), or two or more curing agents may be used in combination. In the present invention, component (B) preferably contains an imidazole compound, and more preferably contains both an imidazole compound and a phenol compound (preferably liquid).
[0045] The LCM material of the present invention preferably contains 1 to 20% by weight of component (B) relative to 100 parts by weight of component (A), more preferably 2 to 17% by weight, and particularly preferably 3 to 15% by weight. When a phenolic compound is blended, the blending amount of the phenolic compound as a curing agent is preferably an amount that provides a stoichiometric equivalent ratio (curing agent equivalent / epoxy group equivalent) with the epoxy resin of 0.00 to 1.00, more preferably an amount that provides an equivalent ratio of 0.05 to 0.50. Even more preferably, the blending amount is an amount that provides an equivalent ratio of 0.08 to 0.30. The blending amount is preferably 0 to 100 parts by weight, more preferably 2 to 15 parts by weight, relative to 100 parts by weight of the (A) epoxy resin. By setting the blending amount within this range, the curing time of the LCM material is not too long, improving the productivity of electronic components, warping is suppressed after the LCM material applied to a wafer on which a semiconductor chip is mounted is cured, and the storage stability of the LCM material can be improved.
[0046] The hardener used as component (B) can be a commercially available product. For imidazole hardeners, the Curazol series (Shikoku Chemical Industry Co., Ltd.) can be used, and for liquid phenol novolac resins, the MEH series (UBE Corporation) can be used, as well as reagents marketed by Tokyo Chemical Industry Co., Ltd., etc.
[0047] [Filler (Component (C))] The LCM material of the present invention contains a filler. The filler is added for the purpose of improving the moisture resistance and thermal cycle resistance, particularly the thermal cycle resistance, of the encapsulated portion when the epoxy resin composition of the present invention is used as an LCM material. Hereinafter, this filler may be referred to as "component (C)".
[0048] The shape of the filler may be any of spherical, amorphous, flaky, etc., and these may be mixed for use. From the viewpoint of high reliability as an LCM material, a spherical filler that can be highly packed is preferable.
[0049] Examples of the filler of component (C) used in the present invention include, but are not limited to, silica, silicon carbide, silicon nitride, alumina (aluminum oxide), aluminum nitride, aluminum borate, aluminum hydroxide, magnesium hydroxide, aluminum silicate, magnesium silicate, calcium silicate, calcium carbonate, magnesium sulfate, barium sulfate, barium carbonate, titanium oxide, magnesium oxide, zinc oxide, lime sulfate, potassium titanate, magnesium carbonate, zinc oxide, boron nitride, zirconia (zirconium oxide), glass beads, mica, clay, kaolin, talc, zeolite, wollastonite, smectite, sepiolite, zonolite, etc. In the present invention, it is preferable that component (C) contains silica. This is because silica also functions as a rheology modifier. Silica may be natural silica (silica stone, quartz, etc.) or synthetic silica (fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, ultrafine amorphous silica, etc.). Synthetic silica can be synthesized by any method, including dry and wet methods. In addition, component (C) may be surface-treated with a surface treatment agent, for example, a coupling agent such as a silane coupling agent (which may have a substituent such as an epoxy group, an amino group, a phenyl group, a vinyl group, or a (meth)acryloyl group). In the present invention, it is preferable that at least a part of component (C) is surface-treated.
[0050] In one embodiment, component (C) comprises silica powder. Silica powder is commercially available. In the present invention, it is more preferable that component (C) contains fused silica powder and / or silica powder produced by a deflagration method. The deflagration method is a method for producing a silica powder consisting of fine spherical silica particles by oxidizing metal silicon powder dispersed in an oxygen stream by ignition, melting or vaporizing the resulting oxide (which may contain unreacted metal silicon) by heating using the reaction heat of the oxidation, and then cooling to a temperature below the melting point of the oxide. On the other hand, examples of fused silica powder include those consisting of spherical silica particles and those consisting of crushed silica particles. From the viewpoint of the fluidity of the LCM material, it is more preferable that component (C) contains silica powder consisting of spherical silica particles (especially those with high sphericity).
[0051] In the LCM material of the present invention, a single filler may be used as component (C), or two or more fillers may be used in combination. When component (C) contains two or more fillers, the fillers may differ in the substance contained in the particles that compose them, or when the fillers are composed of particles containing the same substance, the fillers may differ in the manufacturing method or in some other characteristic (e.g., particle size distribution, which will be described later). In one embodiment, component (C) contains two or more fillers.
[0052] The properties of the particles constituting component (C), such as particle size distribution, are not particularly limited. However, from the viewpoint of an appropriate thixotropic index (described later) of the LCM material, in the present invention, component (C) preferably contains particles having a particle size of 5 nm to 100 nm, more preferably particles having a particle size of 10 nm to 50 nm, in an amount of 5 to 23 wt % and more preferably 8 to 19 wt % based on the total weight of component (C). In this case, the properties of the particles other than the particles having a particle size of 5 nm to 100 nm in component (C) are not particularly limited, except for the content in component (C). The particle size distribution of the particles constituting component (C) can be obtained by analyzing a micrograph (e.g., an electron microscope photograph) taken of a sample of component (C) using image processing software, and quantifying and statistically processing the sizes of all or some of the particles in the micrograph. Here, when component (C) contains two or more types of fillers, the particle size distribution of the particles constituting component (C) refers to the particle size distribution of the particles constituting component (C) as a mixture of all of those fillers. In addition, the particles having a particle size of 5 nm to 100 nm in component (C) are preferably surface-treated. The method of surface treatment is not particularly limited as long as it is a method known to those skilled in the art, and can be performed by contacting the filler with a compound used for surface treatment of the filler, for example, a compound having an epoxy group, a phenylamino group, a methacryl group, or an isocyanate group. The contact with the filler may be performed by directly acting the compound, or a method such as immersing the filler in a solution in which the compound is dissolved in a solvent capable of dissolving the compound and then removing the solvent can be used.
[0053] The LCM material of the present invention preferably contains 65 to 90 wt %, more preferably 68 to 88 wt %, and particularly preferably 70 to 85 wt % of component (C) based on the total weight of the LCM material.
[0054] The filler as component (C) may be commercially available, and the average particle size and other properties may be appropriately selected from the disclosed grades. Examples of commercially available fillers include silica-based fillers such as Aerosil (Nippon Aerosil), Sildex (Asahi Glass), Admafuze, Admafine, and Admanano (Admatechs Co., Ltd.), and alumina-based fillers such as AG2030-SMO (Admatechs Co., Ltd.) and DAB10FCAll (Denka Co., Ltd.).
[0055] (D) Ion trapping agent The liquid compression molding material of the present invention contains an ion trapping agent. The ion trapping agent is a compound that captures ion impurities contained in resins such as (A) epoxy resins. By containing the ion trapping agent, chloride ions (Cl - ) and other anionic impurities, thereby suppressing short circuit defects during operation of the semiconductor package.
[0056] There are ion trapping agents that trap cations and anions, but the ion trapping agent used in the present invention is not particularly limited as long as it can trap chloride ions, and both inorganic and organic compounds can be used. Examples of organic compounds used as ion trapping agents include triazole compounds, tetrazole compounds, and bipyridyl compounds. Examples of inorganic compounds used as ion trapping agents include rare earth oxides, bismuth compounds such as bismuth hydroxide compounds, antimony compounds, titanium compounds, zirconium compounds such as zirconium phosphate having a specific structure, magnesium compounds such as hydrotalcites, and aluminum compounds. Among these, it is preferable to include at least one selected from bismuth compounds, antimony compounds, and zirconium compounds from the viewpoint of further enhancing the chloride ion trapping effect, and it is more preferable to consist of only these compounds. The ion trapping agent may be used alone or in combination of two or more types.
[0057] In the liquid compression molding material of the present invention, the content of the ion trapping agent is preferably 0.2 to 7 parts by mass, more preferably 0.5 to 6 parts by mass, further preferably 1.0 to 5 parts by mass, particularly preferably 1.0 to 4.7 parts by mass, and most preferably 1.2 to 2.4 parts by mass, relative to 100 parts by mass of the epoxy resin (A). By setting the content within this range, the chloride ion concentration in the LCM material can be sufficiently reduced without impairing other properties required of the LCM material.
[0058] The average particle size of the ion trapping agent used in the present invention is preferably 0.01 μm (10 nm) to 3 μm, more preferably 0.1 μm to 2.0 μm, and even more preferably 0.2 μm to 1.5 μm. The upper limit of the average particle size of the ion trapping agent used in the present invention is preferably 3.0 μm or less, more preferably 2.0 μm or less, more preferably 1.8 μm or less, more preferably 1.5 μm or less, more preferably 1.2 μm or less, more preferably 1.0 μm or less, more preferably 0.8 μm or less, more preferably 0.5 μm or less, and particularly preferably 0.4 μm or less, in consideration of the distance between chips and wafers and / or between chips in electronic components including multiple chips stacked 2.5-dimensionally or three-dimensionally, and the distance between bumps in electronic components including multiple bumps. The lower limit of the average particle size of the ion trapping agent is not limited as long as an LCM material that has suitable handleability and can be injected into narrow paths of electronic components is obtained, but is preferably 0.01 μm (10 nm) or more, more preferably 0.1 μm or more, and more preferably 0.2 μm or more. The average particle size of the ion trapping agent is a value measured by the same method as the method for analyzing the particle size and particle size distribution of the (C) filler particles.
[0059] As the ion trapping agent, commercially available products can be used, such as the IXE series and IXEPLAS series manufactured by Toagosei Co., Ltd.
[0060] The LCM material of the present invention preferably has fluidity to the extent that it exhibits a thixotropic index (TI) of 0.8 to 4.0. The TI is more preferably 0.8 to 2.0. In the present invention, the TI of the LCM material is expressed by the following formula: TI=η1 / η 10 (In the formula, η1 is the viscosity of the LCM material measured using a rotational viscometer at a temperature of 25°C and a rotation speed of 2 rpm. η 10 is the viscosity of the LCM material measured under the same conditions as η1, except that the rotation speed was 20 rpm) It is expressed as follows. When the TI is within the above range, the LCM material can be smoothly discharged from the application means. In addition, in the sealing process by compression molding, a certain amount of time is required from when the LCM material is applied to the sealed object until stress is applied, and during this time, the applied LCM material naturally spreads over the sealed object to a certain extent, so that depending on the shape of the mold, the LCM material may overflow from the mold before the mold is completely closed. However, when the TI is within the above range, there is less risk of problems such as leakage from the mold joints occurring. This makes it possible to provide an LCM material with rheological properties that are more suitable for sealing process.
[0061] According to the above definition of TI, when the TI of an LCM material is 1 or less, the viscosity of the LCM material under a relatively high shear stress is the same as or higher than the viscosity of the LCM material under a relatively low shear stress. However, since the viscosity of an LCM material varies depending on the measurement conditions, the behavior of the LCM material under actual compression molding conditions may not match the behavior predicted from the TI defined above.
[0062] An example of a means for achieving such suitable rheological properties, i.e. suitable TI, of an LCM material is to appropriately adjust the particle size distribution of component (C) to include fine particles with particle sizes of 5 nm to 100 nm (e.g., 5 to 23% by weight based on the total weight of component (C)), as described above. This is particularly useful when component (C) contains silica. This is because silica also functions as a rheology modifier.
[0063] An epoxy resin composition prepared using a filler containing the above-mentioned fine particles, which is used as an encapsulant for semiconductors, is disclosed in, for example, Patent Document 6. However, this epoxy resin composition is intended to be used as an underfill agent, and the underfill agent needs to have higher fluidity (e.g., evaluated as "viscosity at 120°C" described below) than the LCM material. For this reason, in this epoxy resin composition, it is not preferable to increase the content of fine particles in the filler beyond a certain level.
[0064] In the present invention, the viscosity of the LCM material at 25° C. is preferably 10 to 1000 Pa·s, more preferably 30 to 900 Pa·s, and even more preferably 50 to 800 Pa·s. In the present invention, the viscosity of the LCM material at 25° C. is determined based on the above η 10 It is measured in the same manner as the measurement of .
[0065] Furthermore, the LCM material of the present invention preferably has a viscosity at 120°C of 0.3 to 6.0 Pa·s, more preferably 0.5 to 5.5 Pa·s, and even more preferably 0.8 to 5.1 Pa·s. In the present invention, the viscosity at 120°C means the viscosity (unit: Pa·s) measured at 120°C after applying a vibration of 10 Hz frequency at 120°C for 1 minute under conditions in which the shear strain is controlled to a constant value using a rheometer. In contrast, the viscosity of an underfill agent at 120°C is usually less than 0.3 Pa·s.
[0066] If desired, the LCM material of the present invention may contain optional components such as those described below, in addition to the above-mentioned components (A) to (D) which are essential components, as necessary.
[0067] · Hardening accelerator The LCM material of the present invention may contain a curing accelerator if desired. The curing accelerator used in the present invention is not particularly limited as long as it is a compound that can accelerate the curing of the epoxy resin (component (A)) by the curing agent (component (B)), and known compounds can be used. Examples of the curing accelerator include basic compounds such as amine compounds and organometallic compounds. It is preferable not to include phosphorus-containing materials such as an adduct of triphenylphosphine and benzoquinone, since the life of the material may be deteriorated if the amount of the material is increased, and the material has the effect of opening the epoxy group ring, which may impair the curability of the LCM material. Examples of the amine compound include 2,4,6-tris(dimethylaminomethyl)phenol, diethylamine, triethylamine, diethylenetetramine, triethylenetetramine, and 4,4-dimethylaminopyridine, etc. The amine compound may be an amine adduct.
[0068] Examples of the organometallic compound include zinc naphthenate, cobalt naphthenate, tin octoate, cobalt octoate, cobalt bisacetylacetonate (II), and cobalt trisacetylacetonate (III).
[0069] When the LCM material of the present invention contains a curing accelerator, the amount of the curing accelerator is preferably 1 to 100 parts by weight, and more preferably 5 to 50 parts by weight, per 100 parts by weight of the total amount of components (A) to (D).
[0070] Pigments The LCM material of the present invention may contain a pigment if desired. By containing a pigment, the chromaticity of the LCM material of the present invention can be adjusted. In addition, considering the possibility that wiring in electronic components may be affected by light, the use of a pigment is important. The pigment is not particularly limited, but for example, carbon black, titanium black such as titanium nitride, black organic pigments, mixed color organic pigments, and inorganic pigments can be used. Black organic pigments include perylene black and aniline black, mixed color organic pigments include those that are pseudo-blackened by mixing at least two or more pigments selected from red, blue, green, purple, yellow, magenta, cyan, etc., and inorganic pigments include graphite, and fine particles of metals and their oxides (including complex oxides), sulfides, nitrides, etc. Examples of the metals include titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, silver, etc. In the LCM material of the present invention, the pigments may be used alone or in combination of two or more types. Furthermore, the pigments may be used in combination with other colorants such as dyes.
[0071] From the viewpoint of heat resistance, the pigment is preferably carbon black. When the LCM material of the present invention contains a pigment, the amount of the pigment is preferably 0.01 to 1 part by weight, and more preferably 0.1 to 0.5 parts by weight, per 100 parts by weight of the total amount of components (A) to (D).
[0072] Stabilizers The LCM material of the present invention may contain a stabilizer if desired. The stabilizer may be contained in the LCM material of the present invention in order to improve its storage stability and extend its pot life. Various stabilizers known as stabilizers for one-liquid adhesives based on epoxy resins can be used, but at least one selected from the group consisting of liquid borate ester compounds, aluminum chelates, and organic acids is preferred because of its high effect of improving storage stability.
[0073] Examples of liquid boric acid ester compounds include 2,2'-oxybis(5,5'-dimethyl-1,3,2-oxaborinane), trimethyl borate, triethyl borate, tri-n-propyl borate, triisopropyl borate, tri-n-butyl borate, tripentyl borate, triallyl borate, trihexyl borate, tricyclohexyl borate, trioctyl borate, trinonyl borate, tridecyl borate, tridodecyl borate, trihexadecyl borate, trioctadecyl borate, tris(2-ethylhexyloxy)borane, bis(1,4,7,10-tetraoxaundecyl)(1,4,7,10,13-pentaoxatetradecyl)(1,4,7-trioxaundecyl)borane, tribenzyl borate, triphenyl borate, tri-o-tolyl borate, tri-m-tolyl borate, and triethanolamine borate. Liquid borate ester compounds are preferred because they are liquid at room temperature (25°C), and therefore the viscosity of the LCM material can be kept low. As the aluminum chelate, for example, aluminum chelate A can be used. As the organic acid, for example, barbituric acid can be used.
[0074] When the LCM material of the present invention contains a stabilizer, the amount of the stabilizer is preferably 0.01 to 30 parts by weight, more preferably 0.05 to 25 parts by weight, and even more preferably 0.1 to 20 parts by weight, per 100 parts by weight of component (A).
[0075] Silicone additives The LCM material of the present invention may contain a silicone-based additive if desired. The inclusion of a silicone-based additive is preferable from the viewpoint of improving the fluidity of the LCM material. The silicone-based additive is preferably a dialkyl polysiloxane (alkyl groups bonded to Si include methyl, ethyl, etc.), particularly dimethyl polysiloxane. The silicone-based additive may also be a modified dialkyl polysiloxane, for example, an epoxy-modified dimethyl polysiloxane. Specific examples of the silicone-based additive include KF69 (dimethyl silicone oil, manufactured by Shin-Etsu Silicone), SF8421 (epoxy-modified silicone oil, manufactured by Toray Dow Silicone), and the like. The silicone-based additive may be used alone or in combination of two or more kinds.
[0076] When the LCM material of the present invention contains a silicone additive, the amount of the silicone additive is preferably 0.1 to 1.0 part by weight, and more preferably 0.25 to 1 part by weight, per 100 parts by weight of component (A).
[0077] Coupling Agent The LCM material of the present invention may contain a coupling agent if desired. The inclusion of a coupling agent, particularly a silane coupling agent, is preferred from the viewpoint of improving adhesive strength. As the coupling agent, various silane coupling agents such as epoxy-based, amino-based, vinyl-based, methacryl-based, acrylic-based, and mercapto-based agents can be used. Specific examples of silane coupling agents include 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, vinyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, etc. These silane coupling agents may be used alone or in combination of two or more.
[0078] When the LCM material of the present invention contains a coupling agent, the amount of the coupling agent is preferably 0.01 to 5 parts by weight, and more preferably 0.1 to 5 parts by weight, per 100 parts by weight of component (A).
[0079] Migration inhibitor The LCM material of the present invention may contain a migration inhibitor if desired. Migration is a phenomenon in which metal in a wiring pattern is eluted by an electrochemical reaction, resulting in a decrease in resistance. The inclusion of a migration inhibitor is preferable from the viewpoint of improving the reliability of electronic components. Specific examples of migration inhibitors include xanthines such as caffeine, theophylline, theobromine, and paraxanthine; tocols such as 5,7,8-trimethyltocoi (α-tocopherol), 5,8-dimethyltocoi (β-tocopherol), 7,8-dimethyltocoi (γ-tocopherol), and 8-methyltocoi (δ-tocopherol); 5,7,8-trimethyltocotrienol (α-tocotrienol), 5,8-dimethyltocoi (β-tocotrienol), and 7,8-dimethyltocoi (γ-tocotrienol); Tocotrienols such as 8-methyltocotrienol (δ-tocotrienol), benzotriazoles such as benzotriazole, 1H-benzotriazole-1-methanol, and alkylbenzotriazoles, triazines such as 2,4-diamino-6-vinyl-S-triazine, 2,4-diamino-6-[2'-ethyl-4-methylimidazole-(1)]-ethyl-S-triazine, and 2,4-diamino-6-methacryloyloxyethyl-S-triazine, and isocyanuric acid adducts of the above benzotriazoles or triazines. These migration inhibitors may be used alone or in combination of two or more.
[0080] When the LCM material of the present invention contains a migration inhibitor, the amount of the migration inhibitor is preferably 0.01 to 5 parts by weight, and more preferably 0.1 to 5 parts by weight, per 100 parts by weight of component (A).
[0081] Other additives If desired, the LCM material of the present invention may contain other additives, such as leveling agents, antioxidants, antifoaming agents, thixotropic agents, viscosity modifiers, flame retardants, solvents, reactive diluents, elastomers, etc., within the scope of the present invention. The types and amounts of each additive are as per usual.
[0082] The method for producing the liquid compression molding (LCM) material of the present invention is not particularly limited. For example, the components (A) to (D) and other additives, if desired, are simultaneously or separately introduced into an appropriate mixer, and if necessary, are stirred and mixed while being melted by heating to obtain a uniform composition, thereby obtaining the LCM material of the present invention. The mixer is not particularly limited, and examples of the mixer that can be used include a Raikai mixer equipped with a stirring device and a heating device, a Henschel mixer, a three-roll mill, a ball mill, a planetary mixer, a bead mill, and the like. These devices may also be used in appropriate combination.
[0083] In the LCM material of the present invention, when component (C) contains particles having a particle size of 5 nm to 100 nm (for example, 5 to 23% by weight based on the total weight of component (C)), the LCM material of the present invention is preferably obtained by a method including a step of pre-mixing at least a portion of the particles having a particle size of 5 nm to 100 nm in component (C) with at least a portion of component (A). The LCM material of the present invention is preferably obtainable by the method described above.
[0084] The liquid compression molding material thus obtained is thermosetting, and at a temperature of 100 to 170° C., it is preferable that it cures in 0.01 to 3 hours, and more preferably in 0.1 to 2 hours.
[0085] The liquid compression molding material of the present invention is suitable for the manufacture of electronic components, particularly semiconductor devices that are sealed by compression molding. More specifically, the liquid compression molding material of the present invention is particularly useful for the sealing process of wafers on which circuit formation has been completed but which have not yet been cut into chips, when manufacturing semiconductor devices in miniaturized packages by wafer level chip size packaging.
[0086] In a semiconductor package containing a plurality of chips that are 2.5-dimensionally mounted or three-dimensionally stacked and that is produced using the liquid epoxy resin composition of the present invention, the distance between the chip and the wafer and / or between the chips is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. In electronic components including a plurality of bumps produced using the liquid epoxy resin composition of the present invention, the average distance between the bumps is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less.
[0087] The present invention also provides a cured product obtained by curing the LCM material of the present invention.The present invention further provides an electronic component comprising the cured product of the present invention.
[0088] Table 1 shows preferred examples of blends when the liquid epoxy resin composition of the present invention is used as an LCM material, but these blends are merely illustrative and are not intended to specify the technical scope of the present invention. When a composition contains multiple substances as each component, the "more preferred blend amount" in the table indicates the total amount of each substance for the relevant components (A) to (D) when multiple types of each are contained.
[0089] [Table 1] EXAMPLES
[0090] The present invention will be described below with reference to examples, but the present invention is not limited thereto. In the following description, parts and % are by weight unless otherwise specified.
[0091] The liquid compression molding (LCM) materials of Examples 1 to 9, Comparative Example 1, and Reference Examples 1 and 2 were prepared by mixing the prescribed amounts of each component using a three-roll mill according to the formulations shown in Table 2. In Table 2, the amount of each component is shown by weight (unit: g).
[0092] Epoxy resin (component (A)) In the examples and comparative examples, the compounds used as component (A) are as follows. (A-1) Glycidylamine type liquid epoxy resin (viscosity at 25°C 1000 mPa s, total chlorine content 5000 ppm, manufactured by Mitsubishi Chemical Corporation, jER630) (A-2) Glycidylamine type liquid epoxy resin (viscosity at 25°C 1000 mPa·s, total chlorine content 1500 ppm, manufactured by Mitsubishi Chemical Corporation, jER630LSD) (A-3) Polytetramethylene glycol diglycidyl ether (viscosity at 25°C: 200 mPa·s, total chlorine content: 500 ppm, manufactured by Mitsubishi Chemical Corporation, YX7400N) (A-4) Bisphenol F type liquid epoxy resin (viscosity at 25°C: 5000 mPa·s, total chlorine content: 200 ppm, Nippon Steel Chemical & Material Co., Ltd., YDF-870GS) (A-5) Bisphenol A type liquid epoxy resin (viscosity at 25°C: 12,000 mPa·s, total chlorine content: 600 ppm, manufactured by Nippon Kayaku Co., Ltd., RE-410S)
[0093] Hardener (Component (B)) In the examples and comparative examples, the compounds used as component (B) are as follows. (B-1) 2,4-diamino-6-(2'-methylimidazolyl)ethyl-1,3,5-triazine (manufactured by Shikoku Chemical Industry Co., Ltd., Curesol 2MZ-A) (B-2) 2-Ethyl-4-methylimidazole (Curesol 2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.) (B-3) Liquid phenol novolac resin (UBE Corporation, MEH-8005)
[0094] Filler (component (C)) In the examples and comparative examples, the compounds used as component (C) are as follows. (C-1) Silica filler (average particle size 0.05 μm, manufactured by Admatechs Co., Ltd., YA050C-SM1) (C-2) Silica filler (average particle size 0.3 μm, manufactured by Admatechs Co., Ltd., SE101G-SMO) (C-3) Alumina filler (average particle size 0.2 μm, manufactured by Admatechs Co., Ltd., AG2030-SMO)
[0095] In the examples and comparative examples, the compounds used as component (D) are as follows. (D-1) Bismuth-based ion trapping agent (average particle size 1.5 μm, manufactured by Toagosei Co., Ltd., IXE-500) (D-2) Antimony / bismuth-based ion trapping agent (average particle size 1.5 μm, manufactured by Toagosei Co., Ltd., IXE-633) (D-3) Zirconium / bismuth-based ion trapping agent (average particle size 0.4 μm, manufactured by Toagosei Co., Ltd., IXEPLAS-B1) (D-4) Zirconium / bismuth ion trapping agent (average particle size 1.5 μm, manufactured by Toagosei Co., Ltd., IXE-6107) (D-5) Magnesium / aluminum-based ion trapping agent (average particle size 6.0 μm, manufactured by Toagosei Co., Ltd., IXE-700D)
[0096] In the examples and comparative examples, the properties of the LCM materials were measured as follows.
[0097] (viscosity) Using a Brookfield HB-DV viscometer (model number: HB-DV1), the viscosity of the evaluation sample immediately after preparation was measured at a liquid temperature of 25° C. and 20 rpm.
[0098] (Injectable) A test wafer was prepared by bonding a 20 mm square silicon chip with a thickness of 300 μm onto a 12-inch silicon wafer using an adhesive so that the gap between the silicon wafer and the silicon chip was 20 ± 10 μm. The 20 mm square silicon chips were bonded to four locations 20 mm from the edge of the silicon wafer, in the east, west, north and south directions. The evaluation sample was applied onto this wafer, and a molding device (Apic Yamada Co., Ltd., WCM-300) was used to mold a silicon wafer with a diameter of 300 mm and a thickness of 775 μm at 120 °C / 420 seconds to a diameter of 292 mm and a thickness of 500 μm. After that, a dryer (Yamato Scientific Co., Ltd., DH412) was used to perform main curing at 150 °C / 60 minutes. The area between the silicon wafer and silicon chip of this cured product was observed using an ultrasonic inspection device (Fine SAT FS300 III, manufactured by Hitachi Power Solutions Ltd.), and areas that were completely filled were rated as "no problem," and areas that were not completely filled were rated as "problematic."
[0099] (Warpage) The cured product obtained above (injectability) was measured for the amount of warping at room temperature using a shadow moire type warping measurement device (AXP2.0, manufactured by Akrometrix).
[0100] (Gel Time) Using an automatic curing time measuring device (manufactured by Cyber Corporation, product name "Madoka"), the evaluation sample (0.3 ml ± 0.1 ml) was placed on a stainless steel plate heated to 120°C, and immediately after placement, the evaluation sample was stirred on a two-axis eccentric (rotation speed 120 rpm, revolution speed 50 rpm) and the time until gelation (torque judgment value was 20%) was measured.
[0101] (Cl - amount) The prepared LCM material was heated at 150°C for 60 minutes to harden the sample, which was then crushed into approximately 5 mm squares. 25 cm3 of ion-exchanged water was added to 2.5 g of this sample, and the sample was placed in a PCT test tank (EHS-221M, manufactured by Espec Corporation, 121°C ± 2°C / humidity 100% / 2 atm tank) for 20 hours, and then cooled to room temperature to obtain an extract, which was used as the test liquid. The Cl content of the test liquid obtained by the above procedure was - The amount was measured using an ion chromatograph (Shimadzu Corporation, CLASS-VP, column IC-A3 used).
[0102] (Bias HAST test of cured material) The HAST test is a reliability test carried out under high temperature and high humidity conditions (e.g., 130°C, 85% relative humidity) that accelerate the corrosion of the inside of electronic components (especially metal parts). In this test, a bias HAST test was carried out under conditions in which a bias voltage was applied to the electronic component being tested. A liquid epoxy resin composition was applied to a comb-shaped electrode consisting of a polyimide film substrate (thickness 38 μm) and copper wiring patterned thereon (wiring width 15 μm, line pitch 30 μm, thickness 8 μm, tin-plated (thickness 0.2 ± 0.05 μm)) to a thickness of 150 μm, and the liquid epoxy resin composition on the comb-shaped electrode was cured by heating at 150°C for 1 hour using a dryer to obtain a test specimen. This test piece was attached to a HAST device (model number: PC-422R8, manufactured by Hirayama Manufacturing Co., Ltd.) and the electrical resistance was continuously monitored with a bias voltage of 3 V applied under conditions of 85% relative humidity and 130°C, and the time (unit: hr) from the start of the test until a short circuit occurred (electrical resistance value falling below 10 kΩ) was measured.
[0103] [Table 2]
[0104] As is clear from Table 2, the LCM material of the present invention fully possesses the properties required for use as an LCM material, such as an easy-to-handle viscosity and gel time, and injectability that enables filling by the compression molding method, while the chloride ion content is reduced compared to Comparative Example 1, which does not contain an ion trapping agent, and it has been found possible to reduce the effect on the wiring of semiconductor elements, etc. Furthermore, the use of an ion trapping agent containing bismuth is more effective (Reference Example 3), and even when an epoxy resin with a high chlorine content is used, it is possible to reduce the chlorine content to a practical level (Reference Example 2). [Industrial Applicability]
[0105] The LCM material of the present invention has an extremely low chloride ion content, and is therefore particularly useful as an encapsulation material for improving the reliability of semiconductor elements, whose reliability is adversely affected by impurity ions.
Claims
1. (A) an epoxy resin; (B) a curing agent; (C) a filler; and (D) an ion trapping agent, Liquid compression molding material.
2. The liquid compression molding material according to claim 1 , wherein the ion trapping agent (D) includes at least one selected from a bismuth-based compound, a zirconium-based compound, and an antimony-based compound.
3. The liquid compression molding material according to claim 1, wherein the content of the ion trapping agent (D) is 0.2 to 7 parts by mass per 100 parts by mass of the epoxy resin.
4. The liquid compression molding material according to claim 1, wherein the content of the ion trapping agent (D) is 1.2 to 2.4 parts by mass per 100 parts by mass of the epoxy resin.
5. The liquid compression molding material according to claim 1, wherein the average particle size of the ion trapping agent (D) is 10 nm to 5 μm.
6. The chloride ions (Cl) contained in the epoxy resin (A) - 2. The liquid compression molding material of claim 1, wherein the amount of .
7. The liquid compression molding material according to claim 1, having a viscosity of 50 to 500 Pa · s when measured using a Brookfield HB-DV viscometer at a liquid temperature of 25 ° C. and 20 rpm.
8. The liquid compression molding material was crushed into 5 mm squares and cured, and the resulting powder was applied at a density of 0.1 g / cm 3 2. The liquid compression molding material according to claim 1, wherein the concentration of chloride ions in an extract obtained by immersing the liquid compression molding material in water for 20 hours at a temperature of 121° C., a humidity of 100%, and an atmosphere of 2 atm is less than 2.5 ppm.
9. The liquid compression molding material according to claim 1, which satisfies at least two of the following conditions (i) to (vi): (i) The (D) ion trapping agent contains at least one selected from a bismuth-based compound, a zirconium-based compound, and an antimony-based compound. (ii) The content of the ion trapping agent (D) is 0.2 to 7 parts by mass based on 100 parts by mass of the epoxy resin. (iii) The average particle size of the ion trapping agent (D) is 10 nm to 5 μm. (iv) The chloride ions (Cl) contained in the epoxy resin (A) - ) is 2000 ppm or less. (v) The viscosity is 50 to 500 Pa·s when measured using a Brookfield HB-DV viscometer at a liquid temperature of 25° C. and 20 rpm. (vi) The liquid compression molding material is crushed into 5 mm squares and then cured, and the crushed product is compressed at a density of 0.1 g / cm 3 In an extract obtained by immersing the sample in water for 20 hours at a temperature of 121° C., a humidity of 100%, and an atmosphere of 2 atm, the chloride ion concentration is less than 2.5 ppm.
10. A semiconductor package obtained by encapsulating a semiconductor element with the liquid compression molding material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sealing material composition and electronic part device
JP2001279057A
Epoxy resin composition, semiconductor sealant and semiconductor device
JP2015105304A
Epoxy resin composition for sealing semiconductor, and semiconductor device
JP2017179185A
Epoxy resin composition for sealing semiconductor, and semiconductor device
JP2021172793A
Liquid resin composition for sealing and electronic component device
WO2018221681A1